Hour Glass Constriction in Advanced Carpal Tunnel Syndrome - Dehghani, Mohammad (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Compressive neuropathy of median nerve is relatively common but development of an hourglass like constriction is a rare phenomenon. The purpose of this study is to show morphologic changes of median nerve in advances carpal tunnel syndrome. METHODS: Eighty patients with thenar atrophy, anesthesia and paresthesia of first, second and third finger and severe changes of EMG-NCV were chosen for surgery. All the cases were operated by classic approach. RESULTS: At ten cases, nerve was constricted in point and in six patients’ area constriction was seen. Internal and external neurolysis was performed in all the cases. In two of them because of the wide and severe constriction, resection and end-to-end repair was performed. All the patients have been examined periodically. Mean follow-up was 12 month (8-40). According to grading, pain degree (from 8-9 pre operation to 3-4 post operation) and two point discrimination (from the mean of 14 mm (13-20 mm) to 8 mm (6-10 mm)) decreased. Grip power was increased from the mean of 10 kg to 21 kg. In 15 cases return of sensation, and in 13 cases improvement of opposition power was seen. CONCLUSION: We recommend epineurolysis for mild to moderate constriction and also end-to-end repair may be needed if extensive and severe constriction was found. It means that if we manage mild to moderate constriction sooner, it can prevent the need for further surgical procedure because of sever constriction.